Toisen tahran tarina : Ym. Sherlock Holmes'in seikkailuja - Doyle, Arthur Conan, 1859-1930 (Salt Lake City, UT : Project Gutenberg, 2014)
"Toisen tahran tarina" by Arthur Conan Doyle is a narrative from the popular Sherlock Holmes series, likely written in the early 20th century. The story follows the iconic detective Sherlock Holmes and his companion Dr. John Watson as they unravel a critical case involving a missing, highly sensitive document that could have significant political repercussions in Europe. The opening sets the stage for a thrilling investigation, emphasizing Holmes' brilliance while introducing engaging characters from the realm of politics. The beginning of "Toisen tahran tarina" reveals the urgency of a high-profile case brought to Sherlock Holmes and Dr. Watson by two prominent officials: Lord Bellinger, a former Prime Minister, and Trelawney Hope, the Secretary of European Affairs. They seek Holmes' expertise to recover a secret letter of utmost importance, which has mysteriously vanished from Lord Hope's possession. As they discuss the potential consequences of the letter falling into the wrong hands possibly triggering conflict in Europe Holmes begins to piece together clues while simultaneously grappling with the perplexity of a recent murder, hinting at interconnected events. The stakes are raised when a startling twist involving the murder of a figure tied to the case strikes Holmes, propelling him into action to solve the mystery while keeping the political ramifications in mind. (This is an automatically generated summary.)
Toisen tahran tarina -- Kuusi Napoleonin rintakuvaa -- Kolme ylioppilasta -- Abbey Grangen murha -- Kadonnut jalkapallonpelaaja -- Kultasankaiset silmälasit -- Charles Augustus Milvertonin seikkailu.
Translations of selected stories from The Return of Sherlock Holmes.
Release date is 2014-04-06
E-text prepared by Tapio Riikonen
Keywords: Holmes, Sherlock (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Detective and mystery stories, English -- Translations into Finnish